Synapse-associated protein 102 – a highly mobile MAGUK predominate in early synaptogenesis - De Los Reyes, Dominique Alexandra; Karkoutly, Mohammad Yaman; Zhang, Yonghong (Frontiers in Molecular Neuroscience, 2023)
Neurodevelopmental and neurodegenerative disorders are primarily characterized by serious structural and functional changes in excitatory glutamatergic synapses in the brain, resulting in many synaptic deficits and aberrant synapse loss. It is a big challenge to reverse these synaptic impairments as a treatment for neurological diseases in the field. Extensive research on glutamate receptors as therapeutic targets has been done but with little success shown in human trials. PSD-95-like MAGUK proteins perform a pivotal role in regulating the trafficking and stability of glutamate receptors that are important to postsynaptic structure and function. MAGUK and MAGUK-modulated synaptic pathways are becoming promising candidates for developing therapeutic targets. As a MAGUK protein, SAP102 is not understood well compared to PSD-95. Here, we review the current research on SAP102 including its synaptic functions and regulation, especially its expression and functions in the early stage of synaptogenesis and the association with neurodevelopmental disorders. This review presents valuable information for future structural and functional studies of SAP102 to reveal its roles in young and mature neurons. It provides clues for developing potential remedies to reverse synaptic impairments and strategies to grow new neurons.